2007
DOI: 10.1111/j.1442-2042.2007.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intravesical potassium sensitivity test and bladder biopsy in patients with chronic prostatitis/chronic pelvic pain syndrome

Abstract: Aim:We evaluated the possibility that patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) might have similar histological and physiological bladder changes as that documented in patients with painful bladder syndrome/interstitial cystitis (PBS/IC). Methods: Thirty-five known patients of CP/CPPS according to the clinical criteria of National Institutes of Health (NIH) were evaluated. The severity of the symptoms was evaluated according the NIH-Chronic Prostatitis Symptom Index. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
16
0
3
Order By: Relevance
“…In a subsequent study in 50 patients with prostatitis, 77% were potassium‐positive compared with 0% in 14 asymptomatic controls [29]. An additional study reported 84% positive PSTs in 31 patients [22]. There was a report that mistakenly performed the PST using a 100 mL volume of fluid instead of 40 mL.…”
Section: Potassium Sensitivity In Symptomatic Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study in 50 patients with prostatitis, 77% were potassium‐positive compared with 0% in 14 asymptomatic controls [29]. An additional study reported 84% positive PSTs in 31 patients [22]. There was a report that mistakenly performed the PST using a 100 mL volume of fluid instead of 40 mL.…”
Section: Potassium Sensitivity In Symptomatic Patient Populationsmentioning
confidence: 99%
“…Patients with IC were tested and compared with asymptomatic control subjects. To date, the international literature contains over 35 published reports on potassium testing in over 3000 patients with IC/painful bladder syndrome (PBS) and the data are very robust, with 80% of patients with IC testing positive [19–25]. Furthermore, several reports included data on about 200 normal subjects and the test was negative in 98.3%[14,18,26,27].…”
Section: The Role Of Urinary Potassium In the Generation Of Bladder Smentioning
confidence: 99%
“…1,3,29,207 In fact, the significant overlap of presenting signs and symptoms between IC/PBS and CP/CPPS has led several investigators to propose that they are different manifestations of the same underlying syndrome. 206,[208][209][210] Recurrent infection, leaky epithelium, neurogenic inflammation, and autoimmunity have all been surmised as potential underlying causes of IC/PBS and CP/CPPS, as well as mast cell activation and degranulation. 208 Expressed prostatic secretions from men with CP/CPPS had increased mast cell tryptase and NGF levels, 211 and a later study confirmed that tryptase and carboxypeptidase A (CPA3), a marker of mast cell activation, were also increased in the urine of CP/CPPS patients.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndromementioning
confidence: 99%
“…The discrepancy might be due to the inhomogeneity of the groups and individual sociocultural variability. As a matter of fact, recent studies suggested that KCl sensitivity test lacks discriminating power and should be used as a diagnostic aid rather than a specific test on which to base the diagnosis, and for research purposes only [29][30][31]. The fact that potassium sensitivity test is not welltolerated among patients with severe symptoms also supported this suggestion [32].…”
Section: Discussionmentioning
confidence: 98%